Bio-compatibility evaluation of the heparin coated extracoporeal blood circuit in open heart surgery based on hemological examinations and electron-microscopic observations for morophological changes of blood cells - KOHNO K.; TAKEUCHI Y.; GOMI A.; NAKATANI H.; SUDA Y.; KITAHARA K.; YAMANAKA M.; TANIGUCHI H.; OHSHIMA K. (Jinko Zoki, 1997)
It has become evident through a number of studies that use of the heparin coated extracorporeal blood ciruit in open heart surgery is effective in suppressing the coagulation, fibrinolysis, and complement systems, which is indicative of the improved biocompatibility of the circuit. Our previous studies focused initially on the effects of the Duraflo II heparin coated blood circuit (heparin bonding: ionic) on the coagulation, fibrinolysis, and complement systems and then on the benefits of this circuit in clinical use such as the need for less heparinization resulting in reduced hemorrhage and the need of administering less blood. With a non-heparin coated circuit as a control, we evaluated the biocompatibility of a different type of heparin coated circuit, the Terumo Hepaface blood circuit system (heparin bonding: covalent), by examining its effects on the coagulation, fibrinolysis, complement, and immune systems as well as morphological changes of blood cells associated with its use. Subjects were 20 adults who underwent CABG for the first time. Though the start of extracorporeal circulation invalved a rise in gramlocyte elastase concentration, the concentration 5 miniuts after the termination of circulation was significantly lower in the patients for whom the heparin coated circuit was used. In this patient group, electron-microscopic examinations revealed only small amounts of erythrocytes, in contrast to noticiable amounts of activated leukocytes with pseudopods observed in the control group. These findings suggest that the heparin coated blood circuit of covalent bonding type is improved in biocompatibility, thus providing less invasive extracorporeal circulation. ヘパリンコ・ティング体外循環回路を使用することにより、凝固、線溶、補体活性の抑制が認められ生体適合性が向上することは様々な報告より明らかなものとなってきた。当施設においてもイオン結合回路、Durafio-ll (Baxter社製)を用いた凝固、線溶、補体系の研究や、ヘパリン減量による出血量、輸血量削減等の臨床的有用性についての研究を行ってきた。今回我々は、ヘパリンの結合方式の異なる共有結合回路、Hepaface (Terumo社製)を用い、凝固、補体、免疫系、ならびに電子顕微鏡による形態学的変化を従来型回路と比較検討した。成人の待機的初回冠血行再建術(CABG)20例を対象とした。結果は、顆粒球エラスターゼは体外循環開始とともに増加したが、ヘパリンコ・ト群で循環後5分で有意に低値であった。電子顕微鏡による形態学的所見では、ヘパリンコ・ト群では、少量の赤血球を認めるのみであったが、対照群は、偽足形成を伴う活性化白血球が目立つ傾向にあった。以上のことより、共有結合型ヘパリンコ・ティング回路は、イオン結合型と同様に、体外循環における侵襲を軽減させ生体適合性が向上することが示唆された。